Perspectives on student affairs in South Africa - Bawa, Ahmed; Mandew, Martin (Martin de Porres Archibald); Speckman, McGlory T. ([publisher not identified], 2014)
The goal of Perspectives on Student Affairs in South Africa is to generate interest in student affairs in South Africa. The papers contained herein are based on best practice, local experience and well-researched international and local theories. The papers in this book deal with matters pertaining to international and national trends in student affairs: academic development, access and retention, counselling, and material support for students coming from disadvantaged backgrounds. They are linked to national and international developments, as described in the first two papers. This publicatio.